Theological Semantics of Al-Quran Verses About The Attributes of Allah - Ahmad Dardiri; Iis Susiawati; Dadan Mardani; Hilda Khoerunisa; Muhammad Lukman Alramdani (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2023)
This article discusses semantics which is a branch of science that discusses the conditions that must be met by symbols so that they can contain meaning. As well as several aspects that become Islamic studies in the scope of ushuluddin, fiqh, usul fiqh and morality. This literature study uses a qualitative approach by collecting data from a descriptive study of the literature. Data analysis uses the semiotic method which is basically part of content analysis which focuses on the side of the sign as a source of meaning. The purpose of this study is to describe the different views on the meaning of Islamic texts after the Prophet Muhammad SAW passed through his life based on his beliefs. The result of this study is that the Islamic texts which give rise to many differences of opinion are verses that are mutasyabihat related to the attributes of Allah, and the interpretation of the verses of the Qur'an in the theological flow is based on the principles they believe in. The two streams, namely Mu’tazilah and Asy'ariyyah, interpret the mustasyabihat verses in the Qur'an based on the principles of their respective streams.